2011
DOI: 10.1371/journal.pbio.1001133
|View full text |Cite
|
Sign up to set email alerts
|

The Glial Regenerative Response to Central Nervous System Injury Is Enabled by Pros-Notch and Pros-NFκB Feedback

Abstract: A gene network involving Notch and Pros underlies the glial regenerative response to injury in the Drosophila central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(175 citation statements)
references
References 80 publications
(110 reference statements)
5
170
0
Order By: Relevance
“…Others have shown that Prospero can activate glial gene expression (Choksi et al, 2006;Kato et al, 2011), and our data here suggested that Prospero might play an active role in instructing astrocytic fate. We misexpressed Prospero specifically in Prospero − LG using R56F03-Gal4 (Fig.…”
Section: Prospero Itself Drives Astrocyte Differentiationsupporting
confidence: 76%
See 4 more Smart Citations
“…Others have shown that Prospero can activate glial gene expression (Choksi et al, 2006;Kato et al, 2011), and our data here suggested that Prospero might play an active role in instructing astrocytic fate. We misexpressed Prospero specifically in Prospero − LG using R56F03-Gal4 (Fig.…”
Section: Prospero Itself Drives Astrocyte Differentiationsupporting
confidence: 76%
“…Astrocyte cell bodies consistently occupied particular regions around the neuropil (Fig. 1I), comparable to their positions seen in third-instar larval VNC (Ito et al, 1995;Kato et al, 2011;Stork et al, 2014). Indeed, among the six astrocytes by hemisegment, three are at dorsal positions, two are more laterally located and one is ventral.…”
Section: Drosophila Astrocytes Infiltrate Specific Neuropil Territoriessupporting
confidence: 65%
See 3 more Smart Citations